CODESRIA Bulletin, No 4 & 5, 2022 - Special Issue I: African Higher Education during COVID-19 and in the Post-pandemic Period - Journal System (CODESRIA Bulletin, 2023)
In this Issue Editorial, Godwin R. Murunga...........................................3 Éditorial, Godwin R. Murunga............................................5 Building Community with Intentionally Equitable Hospitality, Maha Ayham Bali............................................................................7 COVID-19, Gender and Intellectual Engagement: Implications for Higher Education in Africa, Addisalem Tebikew Yallew, Fadzayi Marcia Maruza & Amina Mama..........................9 Higher Education Access for Students with Disabilities in South Africa, Zambia and Zimbabwe amidst COVID-19, Tsitsi Chataika, Sandra Makwembere, Serges Alain Djoyou Kamga, & Masauso Chirwa......................11 The COVID-19 Pandemic and Research in African Higher Education Institutions, Soazic Elise Wang Sonne............................13 The Impact of COVID-19 on African Female Graduate Students-from Motherland to the Diaspora, Elizabeth Bifuh-Ambe, Quinta Kemende Wunseh, Martina Ambe & Laurent Beyala.....................15 South Africa’s Higher Education Quality Assurance Framework: Is It Pandemic Proof?, Patrick Swanzy, Francis Ansah, Douglas Mpondi, Gloria Asamoah & Joy Nyondo...................17 How should Makerere University Ensure Quality Learning during the Covid-19 Pandemic?, Florence Ndibuuza & Ronald Bisaso ...........................19 Covid-19 and Knowledge Production in Africa: Entrenching Inequalities or Promising Opportunities?, Samuel Fongwa, Bertha Kibona, Ishmael Munene, Ntimi Mtawa & Gerald Wangenge-Ouma......................................21